Industrial policy, progressive derisking, and the financing of Europe's green transition - Viktor Skyrman (Austrian Foundation for Development Research (ÖFSE), 2024)
To address Europe's environmental, economic, and geopolitical challenges, the European Commission has decided to proactively accelerate digital transformation and decarbonization through industrial policies. As the annual green investment gap exceeds 2 percent of the EU's GDP, of particular relevance is not least how the EU's industrial programs will be financed. Amid scarce fiscal resources and public sector austerity, paradigmatic cases of (financial) derisking aiming to "escort" private finance to green but unprofitable investments have been key to European policymakers' aim to accelerate the green transition. This paper offers two contributions in this context. Firstly, it examines to what extent and how finance for industrial policy has been provided in Europe since the early 2020s. Secondly, it conceptually advances the political economy of derisking literature by elaborating on progressive derisking and Big Green State policies as alternative industrial policy financing programs, and discusses those programs in relation to Europe's macrofinancial regime.
Keywords: 330; Industrial policy; derisking; macrofinancial regimes; climate change; the green transition; digital transformation; European policy studies; political economy; development finance; financialization